Effect of Grinding the Herb and Boiling the Infusion on Total Phenolic Content and Antioxidant Capacity of Herbal Infusions - Karam Kharobi; Lina Soubh (Journal of Pharmacy and Nutrition Sciences, 2019)
Herbal infusions are one of the most consumed beverages in the world. The object of this work was to estimate the phenolic content and evaluate the antioxidant capacity of Cumin seeds (Cuminum cyminum L.) and Anise seeds (Pimpinella anisum L.) infusions, and study the effect of grinding the herb and boiling the infusion on that. The total phenolic content (TPC) was determined by Folin-Ciocalteu method, and the antioxidant capacity was evaluated by two methods, DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay and FRAP (ferric reducing antioxidant power) assay. The TPC and antioxidant activity have increased by grinding the herb and boiling the infusion. By grinding, the TPC and antioxidant activity have nearly multiplied.